Second-Order Two-Scale Computational Method for Nonlinear Dynamic Thermo-Mechanical Problems of Composites with Cylindrical Periodicity (Communications in Computational Physics, 2018)
In this paper, a novel second-order two-scale (SOTS) computational methodis developed for nonlinear dynamic thermo-mechanical problems of composites withcylindrical periodicity. The nonlinearities of these multi-scale problems were causedby the temperature-dependent properties of the composites. Firstly, the formal SOTSsolutions for these problems are constructed by the multiscale asymptotic analysis.Then we theoretically explain the importance of the SOTS solutions by the error analysisin the pointwise sense. In addition, a SOTS numerical algorithm is proposed indetail to effectively solve these problems. Finally, some numerical examples verify thefeasibility and effectiveness of the SOTS numerical algorithm we proposed.